Make computational thinking course full of fun - Tan, Jin Ting (2019)
In recent years, the popularity of Computing course has increased, and more students from different backgrounds are trying to learn the subject. As programming is usually very technical and complex, it might be difficult for students who are new and with little computer literacy. There are many learning and teaching methods that can be utilized to teach programming. These methods can receive various learning outcome and student engagement due to the technicality of the course. Therefore, the aim of this project is to research and evaluate the current methods used to learn Computing course and find out ways to make learning fun. After deciding on the method, a system will be built to help students learn the Computing course.